2015
DOI: 10.1186/s12909-014-0275-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of medical students recall of factual knowledge using learning objects and repeated testing in a novel e-learning system

Abstract: BackgroundSpaced-repetition and test-enhanced learning are two methodologies that boost knowledge retention. ALERT STUDENT is a platform that allows creation and distribution of Learning Objects named flashcards, and provides insight into student judgments-of-learning through a metric called ‘recall accuracy‘. This study aims to understand how the spaced-repetition and test-enhanced learning features provided by the platform affect recall accuracy, and to characterize the effect that students, flashcards and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 80 publications
(102 reference statements)
1
21
0
3
Order By: Relevance
“…Judgments of knowledge together with other student activity metrics may provide data for a next generation of intelligent tutoring systems able to track, manage, and predict student performance [ 130 ]. An increase in studies reporting online activity measurements and correlations with other learning outcomes using reproducible tools, as described before, would generate useful evidence on the effectiveness of CBL methods in enhancing learning [ 131 ]. Metrics could include, for example, student communication style and sentiment [ 132 , 133 ] and time spent on different types of materials [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…Judgments of knowledge together with other student activity metrics may provide data for a next generation of intelligent tutoring systems able to track, manage, and predict student performance [ 130 ]. An increase in studies reporting online activity measurements and correlations with other learning outcomes using reproducible tools, as described before, would generate useful evidence on the effectiveness of CBL methods in enhancing learning [ 131 ]. Metrics could include, for example, student communication style and sentiment [ 132 , 133 ] and time spent on different types of materials [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the online setting, the duration of events showed a great variety between studies. Information or questions were distributed through online sources daily 22,[27][28][29][30]33,34,37,55,85 (n = 10), every 2 days 19,23,24,31,52,53,64,78 (n = 8), every 3 days 41 (n = 1), wee kly 20,35,36,39,40,43,44,71,80,[114][115][116] (n = 12), every 2 weeks 45 (n = 1), or monthly 43,79 (n = 2). In studies explicitly stating that material was not only spaced but also repeated, repetition delays ranged from various days 22,55 (n = 2), to weeks 19,23,24,[27][28][29][31][32][33][34][35][39][40][41]…”
Section: Applying Spaced Learningmentioning
confidence: 99%
“…13,14 This "testenhanced learning" improved learning, especially when used after studying to gauge knowledge and practice recall in a number of settings. 15,16 Larsen et al documented this long-term impact even in postgraduate neurologists and also found it superior to repeated studying alone. 16 The benefit of using formative self-assessments is also seen when comparing populations of students who take quizzes and those who do not routinely use quizzes.…”
Section: Discussionmentioning
confidence: 99%